Peran Pendidikan Sains dalam Mengembangkan Kompetensi Masa Depan di Sekolah Dasar: Kajian Pustaka - Anandea Nurmutia Herdiana; I Wayan Suastra; I Made Citra Wibawa; Ida Bagus Putu Arnyana (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to analyze the role of science education in elementary schools in developing 21st-century competencies, particularly scientific literacy, critical thinking, and science process skills, based on relevant studies published from 2020 to 2025. The method used was a literature review through analysis and synthesis of various studies related to science education at the elementary level. The results showed that inquiry-based and contextual science learning approaches integrated with local wisdom, supported by innovative media such as digital technology and simple experiments, effectively improve students’ cognitive abilities, scientific attitudes, and readiness to face increasingly complex future challenges. In conclusion, science education in elementary schools plays a strategic role as a foundation for developing 21st-century competencies, therefore pedagogical strengthening is needed to optimize its implementation from an early stage.  Keywords: Critical Thinking, Elementary Science Education, Scientific Literacy